The Self-Concept of Earthquake Victims: Phenomenology in the Village Community of Nagrak, Cianjur, West Java - Djuhardi, Lidia; Trifonia; Felicia (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This research is about victims of the Cianjur earthquake which occurred in November 2022. The purpose of this study is to reveal the self-concept of victims of the Cianjur earthquake, especially in Nagrak village, which has the highest number of victims. The research method used is qualitative, with phenomenology as a study of analyzing the experiences of victims namely the experiences of individuals directly affected by the Cianjur earthquake disaster. The research informants were Nagrak villagers consisting of six people namely three women and three men. The theories used are Herbert Mead's symbolic interaction theory, a theory related to self-concept, and Alfred Schutz's phenomenology theory, a distinctive theory with intersubjective meaning. The results showed that the self-concept of the people of Nagrak village affected by the earthquake considered that the earthquake event was an unforgettable traumatic experience because it was so powerful and destroyed most of their lives. The conclusion of the research shows that the self-concept of the people of Nagrak village as victims of the earthquake disaster, shows a traumatic attitude (bad experience) but seems to try to understand the traumatic feeling wisely.